2020
DOI: 10.1136/thoraxjnl-2020-215732
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory evaluation of SARS-CoV-2 lateral flow assays for use in a national COVID-19 seroprevalence survey

Abstract: BackgroundAccurate antibody tests are essential to monitor the SARS-CoV-2 pandemic. Lateral flow immunoassays (LFIAs) can deliver testing at scale. However, reported performance varies, and sensitivity analyses have generally been conducted on serum from hospitalised patients. For use in community testing, evaluation of finger-prick self-tests, in non-hospitalised individuals, is required.MethodsSensitivity analysis was conducted on 276 non-hospitalised participants. All had tested positive for SARS-CoV-2 by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
168
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(175 citation statements)
references
References 24 publications
5
168
1
1
Order By: Relevance
“…130 However, in the UK, nationally validated assays have been evaluated with convalescent samples from community participants and a number of large-scale serosurveys now use these. [131][132][133] Clear understanding of the kinetics of the response, particularly for the specific N and S antigens, is important for the interpretation of seroprevalence studies.…”
Section: Implications For Policymentioning
confidence: 99%
“…130 However, in the UK, nationally validated assays have been evaluated with convalescent samples from community participants and a number of large-scale serosurveys now use these. [131][132][133] Clear understanding of the kinetics of the response, particularly for the specific N and S antigens, is important for the interpretation of seroprevalence studies.…”
Section: Implications For Policymentioning
confidence: 99%
“…As people who have had SARS-CoV-2 previously confirmed by PCR would probably be less likely to seek antibody testing than other people, we consider this lower estimate (84.7%) to be a more appropriate estimate of test sensitivity for a potential use case in which people were to choose to take the test to find out their own previous infection status. For an alternative potential use of population serosurveillance,34 the estimate of test sensitivity of 86.6% (83.2% to 89.4%), which derives from an analysis of all EDSAB-HOME stream A and B participants, irrespective of PCR positivity, may be more appropriate. Finally, we observed that AbC-19 test bands were often weak, a finding also reported in another laboratory based evaluation of AbC-19 16.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous evaluations of LFIAs have used a “two gate” design, in which tests are performed on two groups of samples: PCR positives and pre-pandemic sera 24202122. This study design remains an important tool in evaluating accuracy, owing to the lack of a gold standard test, as discussed above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this this version posted September 27, 2020. ; https://doi.org/10.1101/2020.09.25.20183459 doi: medRxiv preprint sensitivity (21% to 92%), that was significantly inferior to ELISAs performed on venous blood (Flower et al, 2020). Studies have shown high sensitivity of ELISAs for the detection of SARS-CoV-2 antibodies in venous blood (Adams et al, 2020;Lisboa Bastos et al, 2020;Staines et al, 2020).…”
Section: Introductionmentioning
confidence: 99%